Assessment and Prediction of Salivary Gland Function After Head and Neck Radiotherapy: A Systematic Review - J. Le Guevelou; X. Palard‐Novello; E. Kammerer; M. Baty; M. Perazzi; A. Larnaudie; R. De Crevoisier; J. Castelli (Cancer Medicine)
ABSTRACT Background Modern imaging techniques with magnetic resonance imaging (MRI) or positron emission tomography/computed tomography (PET/CT) have recently been developed to assess radiation‐induced damage to salivary structures. The primary aim of this review was to summarize evidence on the imaging modalities used for the assessment and prediction of xerostomia after head and neck radiotherapy (RT). Methods A systematic review of the literature was performed using successively the MeSH terms “PET,” “MRI,” “scintigraphy,” “xerostomia,” and “radiotherapy.” Results Salivary excretion flow following head and neck RT is correlated with the dose delivered to both parotid and submandibular glands. Salivary gland standardized uptake value extracted from PET/CT following RT has been shown to be correlated with SEF. Models including early SUV decline or ADC increase during RT and clinical parameters can help predict the loss of salivary function after RT. Conclusions Modern imaging parameters appear to be correlated with salivary gland scintigraphy parameters. Models including functional parameters extracted from either PET/CT or MRI unveil new possibilities for adaptive treatment in a selected population of patients.